Selective screening of 650 high risk Iranian patients for detection of inborn error of metabolism - Narges Pishva; Alie Mirzaee; Zohre Karamizade; Shahnaz Pourarian; Fariba Hemmati; Mostajab Razvi; Forough Saki (Mashhad University of Medical Sciences, 2015)
Objective: Although metabolic diseases individually are rare ,but overall have an incidence of 1/2000 and can cause devastating and irreversible effect if not diagnosed early and treated promptly. selective screening is an acceptable method for detection of these multi presentation diseases.Method: using panel neonatal screening for detection of metabolic diseases in 650 high risk Iranian patients in Fars province. The following clinical features were used as inclusion criteria for investigation of the patients.Lethargy, poor feeding ,persistent vomiting, cholestasis, intractable seizure ,decreased level of consciousness ,persistent hypoglycemia, unexplained acid base disturbance and unexplained neonatal death.Result: Organic acidemia with 40 cases (42%) was the most frequent disorder diagnosed in our high risk populations, followed by disorder of galactose metabolism(30%), 15 patient had classic galactosemia(GALT